The Effects of Acute Stress on Inhibitory Control in Individuals with Problem Gambling - Froude, Anna Marie (My University, 2024)
Background: Poor inhibitory control is a hallmark of problem gambling (PG), which is characterised by frequent gambling and unsuccessful efforts to control/stop gambling. Stress and PG demonstrate a cyclical relationship, whereby gambling can act as a coping mechanism for dealing with stressful life events, while consistent gambling engagement can increase stress. To date, few studies examine acute stress effects on inhibitory control (IC) in this group. Purpose: This study compares acute stress effects on IC in PG and healthy control (HC) populations. Methods: Twenty participants with PG and twenty HCs completed self-report measures of mood disturbance (Profile of Mood States; POMS) and impulsivity (Barratt Impulsiveness Scale); saliva samples were collected to measure cortisol. The Trier Social Stress Test was administered to induce an acute stress response, followed by the Stop-Signal Task (SST), a validated measure of IC. Results: Subjective stress responses increased over time in both groups, with the PG group demonstrating significantly higher POMS ratings (p<.05), however, no differences in cortisol levels were observed between groups (p>.05). Moreover, no group differences were observed on the SST (p>.05). Exploratory correlations revealed significant positive and negative correlations between cortisol levels and ‘go’ reaction time and ‘stop’ signal reaction time on the SST, respectively (p<.05). Conclusion: This study is the first, to our knowledge, to directly examine acute psychosocial stress effects on IC in individuals with PG. Our findings show that while both groups display similar cortisol levels, individuals with PG report increased subjective stress relative to HCs. Despite no stress-induced impairments on SST performance, significant correlations were observed between task reaction time and cortisol levels in the PG group. This study helps to better inform clinical practice by providing a comprehensive understanding of the implications of stress and IC on gambling behaviours.
Keywords: Problem Gambling; Acute Stress; Inhibitory Control; Addiction